The theo-centrical model for environmental ethics - Ciszek, Mariusz (Studia Ecologiae et Bioethicae, 2006)
The author presents in his article the following problems: the theo-centrical aspect of environmental ethics, the anthropological foundations of eiwironmental ethics in Tomism, problems of protecting the social natural environment in the light of moral theology, natural law in its ecological dimensions, the understand of conscience in this field of study, sins against the environment, ecological aspects of arotology, and the Decalogue for the environment.